Pengaruh Penyuluhan Perorangan dengan Media Lembar Balik terhadap Tingkat Pengetahuan Ibu Balita dalam Pemberian MP-ASI pada Balita BGM Usia 6-59 Bulan Dilingkungan Babakan Kebon - Endika Putra; Susilo Wirawan; Lalu Khairul Abdi; Irianto Irianto (Poltekkes Kemenkes Mataram, 2020)
Background: Data on the assessment of nutritional status in West Nusa Tenggara in 2016 lack of nutrition problems increased, namely in 2016 as many as 15.6% while in 2017 there was an increase of 19.1%. From the data from the SKDN Babakan health center in 2017 it was found that there were still high fives who experienced malnutrition status. This can be seen from the data below the red line in Babakan health center, one of the high-fives health center working areas. 40 toddlers. Below the red line is a severe level of malnutrition so that when weighed the weight is below the red line on the card towards health. An understanding of how to provide proper food so that children want to eat is still not widely known and often does not provide complementary food for breast milk by reason of their children not wanting to eat. This study aims to determine the level of knowledge of mothers of children under five after counseling. The Purpose Of Study : The purpose of this study was to determine the effect of individual counseling with media backsheet on the knowledge of mothers of children under five in the provision of complementary food for breast milk in infants under the age of 6 - 59 months. Methods: This study was conducted in April. This type of research is experimental using the design of the one group pretest posttest. The sample used in this study used saturated samples or used all populations as samples. Data analysis using analysis of Wilcoxon Sign Rank with the help of computers. Counseling of individuals is carried out 3 meetings for 50 minutes each meeting for 23 days. It is expected to increase the knowledge of mothers of children under five in the provision of complementary food for breast milk Results: The results of the study showed that there was an influence of individual counseling on increasing the knowledge of mothers under five about giving MP-ASI, with a value (p = 0.00 <0.05) Conclusion : : Increased knowledge of mothers of children under five in providing complementary food for breast milk to infants Under the red line after being given counseling with flipchart media.